واقع شبكة النقل في العراق (Journal of Planner and Development, 2011)
Transportation network could be considered as a function of the developmental level of the Iraq, that it is representing the sensitive nerve of the economic activity and the corner stone for the implementation of development plans and developing the spatial structure. The main theme of this search is to show the characteristics of the regional transportation network in Iraq and to determine the most important effective spatial characteristics and the dimension of that effect negatively or positively. Further this search tries to draw an imagination for the connection between network as a spatial phenomenon and the surrounded natural and human variables within the spatial structure. This search aiming also to determine the nature of the regional transportation of Iraq, how it has been developed, what are its characteristics, types, and patterns that have been came from the spatial differentiation in the region to evaluate it spatially and as an indicator for the socio-economic development in the study area(Iraq(